PERCEPTIONS OF THE NON-ENGLISH DEPARTMENT LECTURERS TOWARDS CLIL IN HIGHER EDUCATION - Fitri Budi Suryani (JALL (Journal of Applied Linguistics and Literacy), 2017)
Content and Language Integrated Learning (CLIL) is an approach to learning activity that uses foreign language as a medium for learning content so that the competence on the language and the subject area content can be achieved simultaneously. CLIL can be implemented in elementary level, secondary level, as well as tertiary or higher education level. In higher education, CLIL might have two significant reasons to be implemented: the globalized world and university internationalization. So far in Indonesia, nearly all universities have not implemented CLIL yet. This study aims at finding out the lecturers’ perceptions towards CLIL in higher education. The participants of the study were thirty-three lecturers from non-English departments of Universitas Muria Kudus. The intrument to collect the data was closed-ended questionnaire. The result reveals that the non-English department lecturers quite disagree for CLIL to be implemented in higher education. Their objection for having English as a medium of instruction seems to lie in their own ability of English as well as their students’ poor English proficiency. Keywords: CLIL, higher education, non-English department lecturers